Nanoscale segregation of channel and barrier claudins enables paracellular ion flux - Hannes Gonschior; Christopher Schmied; Rozemarijn Eva Van der Veen; Jenny Eichhorst; Nina Himmerkus; Jörg Piontek; Dorothee Günzel; Markus Bleich; Mikio Furuse; Volker Haucke; Martin Lehmann (Nature Communications, 2022)
Meshworks of claudin polymers control the paracellular transport and barrier properties of epithelial tight junctions. Here, the authors show different claudin nanoscale organization principles, finding that claudin segregation enables barrier formation and paracellular ion flux across tight junctions.